2020
DOI: 10.3329/jbsp.v15i1.48112
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D<sub>3</sub> supplementation on plasma antioxidant enzymes in D<sub>3</sub> deficient patients with COPD - a randomized controlled trial

Abstract: Background: Free radical is a crucial factor for progression of COPD. Antioxidant enzymes, including superoxide dismutase (SOD) and catalase (CAT) have been well known to reduce morbidity of chronic disease. Vitamin D3 has antioxidant effect in human body. Objectives: To assess the effects of D3 supplementation on plasma SOD and CAT levels in D3 deficient COPD patients. Method: A double blinded placebo controlled randomized clinical trial was carried out on 30 vitamin D3 deficient male, smoker and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ghodrati et al performed a clinical trial and found out the curative role of this vitamin in treating dyspnea in COPD patients [44]. Supplementation can seemingly reduce the progression and morbidity of chronic diseases by decreasing the number of free radicals with antioxidant enzymes, as observed in the latest randomized control trial performed in Bangladesh by Anjum et al [45]. PRECOVID and Lung VITAL are two large ongoing clinical trials with registration numbers NCT02122627 and NCT01728571, respectively.…”
Section: Clinical Trials Demonstrating the Role Of Supplemental Vitammentioning
confidence: 99%
“…Ghodrati et al performed a clinical trial and found out the curative role of this vitamin in treating dyspnea in COPD patients [44]. Supplementation can seemingly reduce the progression and morbidity of chronic diseases by decreasing the number of free radicals with antioxidant enzymes, as observed in the latest randomized control trial performed in Bangladesh by Anjum et al [45]. PRECOVID and Lung VITAL are two large ongoing clinical trials with registration numbers NCT02122627 and NCT01728571, respectively.…”
Section: Clinical Trials Demonstrating the Role Of Supplemental Vitammentioning
confidence: 99%